Prevalence of Fasciola Infection in Slaughtered Animals in Kashmir (Global Journal of Medical Research, 2017)
Fasciolosis is denoted as a significant veterinary health problem. During current study, a total of 714 cattle slaughtered at different abattoirs of Srinagar city (J&K) were examined for the presence of Fasciola sps in the liver from January 2014 to January 2016. There was moderate prevalence of 26.84% in the studied area. Predominance of Fasciola gigantica (20.86%) was seen as compared to Fasciola hepatica (3.361%) infection with mixed infection of 2.66%. Epidemiological determinants like age, gender, breed and body condition showed statistically significant (p
Keywords: epidemiology; fasciola; cattle; abattoir and srinagar